2022
DOI: 10.1186/s12875-022-01947-w
|View full text |Cite
|
Sign up to set email alerts
|

General practitioner care in nursing homes during the first wave of the COVID-19 pandemic in Germany: a retrospective survey among nursing home managers

Abstract: Background Though evidence on the detrimental impact of the COVID-19 pandemic in nursing homes is vast, research focusing on general practitioners’ (GP) care during the pandemic in nursing homes is still scarce. Methods A retrospective online survey among 1,010 nursing home managers in Germany was conducted during the first wave of the COVID-19 pandemic between November 2020 and February 2021. Associations between perceived deficits in GP care (rou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 33 publications
0
3
0
1
Order By: Relevance
“…Previous articles on nursing home interventions during the COVID-19 pandemic have reported that medical teams had to provide medical care only within their facilities despite the various difficulties they faced [ 10 - 12 ]. Moreover, some studies have emphasized the importance of structural control measures during the pandemic [ 13 , 14 ]. Referring to the literature, we discuss the countermeasures against infectious disease pandemics in long-term care facilities, dividing them into three phases: 1) preventing mass infection, 2) outbreak response, and 3) recovery from outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Previous articles on nursing home interventions during the COVID-19 pandemic have reported that medical teams had to provide medical care only within their facilities despite the various difficulties they faced [ 10 - 12 ]. Moreover, some studies have emphasized the importance of structural control measures during the pandemic [ 13 , 14 ]. Referring to the literature, we discuss the countermeasures against infectious disease pandemics in long-term care facilities, dividing them into three phases: 1) preventing mass infection, 2) outbreak response, and 3) recovery from outbreaks.…”
Section: Discussionmentioning
confidence: 99%
“…Zu berücksichtigen ist auch, dass durch Quarantänemaßnahmen geänderte Lebensbedingungen sich auf die Ausprägung neuro-kognitiver Störungen auswirken können [13]. Erste Hinweise gibt es auch, wie sich die Rahmenbedingungen von hausärztlicher Tätigkeit in Heimen strukturell geändert haben und Folgen für die Patientenversorung aufweisen [14]. In einer eigenen Studie konnten wir zeigen, dass die kognitiven Störungen im Rahmen einer COVID-19-Erkrankung zunahmen, aber dass dies im Praxisalltag ein sehr seltenes Ereignis darstellte [15].…”
Section: Methodenunclassified
“…Recent studies have shown that burnout has been linked to nurses' intention to quit the profession [8,26,35]. It was reported that moderate to high burnout has been reported among nurses and other healthcare professionals [7,8,26].…”
Section: Lack Of Organization/administration Supportmentioning
confidence: 99%
“…Recent studies have shown that burnout has been linked to nurses' intention to quit the profession [8,26,35]. It was reported that moderate to high burnout has been reported among nurses and other healthcare professionals [7,8,26]. High workload, years of practice, resilience, inadequate staffing, and lack of leadership support have been identified as some of the highest complaints amongst healthcare workers.…”
Section: Lack Of Organization/administration Supportmentioning
confidence: 99%